Oil price and economic growth in Kenya: A trivariate simulation - Odhiambo, Nicholas M; Nyasha, Sheilla (International Journal of Sustainable Energy Planning and Management, 2019)
In this study, the dynamic causal relationship between oil price and economic growth in Kenya has been explored during the period from 1980 to 2015. A trivariate Granger-causality framework that incorporates oil consumption as an intermittent variable – in an effort to address the omission-of-variable bias – has been employed. Using the newly developed ARDL bounds testing approach to co-integration and the Error-Correction Model-based Granger-causality framework, the results of the study reveal that there is distinct unidirectional Granger-causality flowing from economic growth to oil price in the study country. These results were found to apply both in the short run an in the long run. Thus, it can be concluded that in Kenya, it is the real sector that pushes oil prices up. Further, it is possible to predict oil price changes in Kenya – given the changes in economic growth.